Age-related differences in men's preferences and barriers to healthcare: Insights from a national Australian survey. - Robert Palmer; James Kite; Philayrath Phongsavan; Timothy J Moss; Bernie Marshall; Nicole Halim; Ben J Smith (PLoS ONE)
Objectives The high burden of preventable disease among men in many countries has highlighted the urgency of promoting stronger engagement by men in health services and programs. In order to inform prevention and early intervention strategies in Australia, this study aimed to examine how age and other socio-demographic factors moderate help-seeking preferences among men in this population, and the major psychosocial and practical barriers to healthcare use for men across the life course. Design Cross-sectional survey using a nationally representative sample. Setting Online survey in March 2021. Participants English-speaking Australian men aged 18-years and older, recruited using a probabilistic sampling method. Of the 1,409 men invited to participate, 1,282 (91%) completed the survey. Main outcome measures Preferences for help-seeking related to physical and mental health, and psychosocial and practical barriers to help-seeking. Results Compared to men aged 70 years and over, younger men were less likely to choose professional sources of help, with those aged 18-29 years showing the lowest odds when needing assistance for physical (OR = 0.28, 95% CI 0.17-0.49) and mental health (OR = 0.28, 95% CI 0.16-0.46). Men in this youngest age group also reported experiencing more practical barriers to healthcare access with 77 out of 241 (32%) men experiencing three or more barriers to healthcare engagement, compared to 16 out of 172 (9.3%) men over 70 years. Multivariable analysis showed that younger age was associated with higher psychosocial barriers to help-seeking. Conclusions Age is a significant factor in men's health help-seeking preferences in Australia and these findings highlight the unique help-seeking profile of younger men. Younger Australian men are less likely to seek help proactively, and encounter more practical and psychosocial barriers than older men. The findings underscore the necessity for public health strategies to engage younger men effectively in proactive health management.